Development and material properties of poly(lactic acid)/poly(3-hydroxybutyrate-co−3-hydroxyvalerate)-based nanocrystalline cellulose nanocomposites - Dasan, Y.K. (John Wiley and Sons Inc., 2017)
This study is focused on the development and analysis of the thermal and structural behavior of nanocrystalline cellulose (NCC)-based bionanocomposites (BCs). Nanocrystalline cellulose was prepared by controlled acid hydrolysis of oil palm empty fruit bunch fibers. The resulting NCC was surface modified using TEMPO-mediated oxidation and solvent exchange methods for surface functionalization and also to improve dispersion of fillers. Solvent exchange NCC reinforced polymer blend containing poly(lactic acid)/poly-(3-hydroxybutyrate-co-3-hydroxyvalerate) was prepared by using solution casting technique at various NCC loading percentages. The addition of NCC resulted in the improvement of structural, thermal, and mechanical properties of BCs as compared to that of the polymer blend. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 44328. © 2016 Wiley Periodicals, Inc.